Cranial neurolymphomatosis and its oncologic counterparts: Case series on malignant cranial nerve neuropathies - Bahadar S Srichawla; Abigail Bose; Vincent Kipkorir (SAGE Open Medical Case Reports, 2024)
Neurolymphomatosis occurs due to the infiltration of a nerve by malignant cells. Cranial neurolymphomatosis is a rare disease process associated with non-solid tumors (i.e., lymphoma, leukemia, etc.). Cranial neurolymphomatosis presents with single or multifocal neuropathy. Primary cranial neurolymphomatosis is defined as the initial presenting symptom leading to a new diagnosis of cancer. Secondary cranial neurolymphomatosis is defined as cancer progression with spread to a cranial nerve. While cranial neurolymphomatosis is a recognized cause of cranial nerve neuropathies, a myriad of other malignancies can also lead to similar clinical manifestations. This case series elucidates not only the classical presentations associated with cranial neurolymphomatosis but also introduces other oncologic entities that may compromise cranial nerve functions. A descriptive case series is presented on six patients with malignancy-related cranial neuropathy who came to a tertiary-care center from 2018 to 2022. 5/6 (83.3%) of patients presented with primary cranial neuropathy. Diffuse large B-cell lymphoma was the most prevalent malignancy observed in 3/6 (50.0%) cases. Other malignancies observed include non-Hodgkin lymphoma, monoclonal B-cell lymphocytosis, and peripheral T-cell lymphoma. The most affected cranial nerve was the trigeminal nerve in 4/6 (66.6%) individuals. Multiple cranial neuropathies were seen in 2/6 (33.3%) of patients. The most common neuroradiographic finding was a lesion to Meckel’s cave. Other cranial nerves affected include the optic, facial, and vestibulocochlear nerves. Diagnostic modalities utilized included magnetic resonance imaging and 18 F-fluoro-2-D-glucose positron emission tomography-computerized tomography. Cerebrospinal fluid analysis for flow cytometry may also have diagnostic value in patients with increased disease burden. Treatment was guided according to individual malignancy and 2/6 (33.3%) patients achieved complete remission, 2/6 (33.3%) died within 1 year, and 1/6 (16.6%) were referred to hospice. Cranial neuropathy may be the first symptom of a neoplastic process; thus, prompt recognition and treatment may improve morbidity and mortality.